Penerapan Pembelajaran Humanisme dalam Pembentukan Karakter Siswa - Widia Ningsi; Sedya Santosa (Universitas Batanghari Jambi, 2023)
Learning activities are processes of interaction and knowledge transactions between teachers and students. The role of character cannot be separated from education to form quality human beings. In humanism, students are learning centers, while the role of the teacher is as a facilitator. In essence, everyone's character is influenced by every thing that is done in life. This happens because character is indeed formed from habits that are carried out and can also be formed through the outside environment. As an educational institution, schools have a role to develop the potential of students. This study uses a qualitative approach which explains how humanist learning is applied, especially in instilling good character in students. The data analysis technique used is data reduction, data presentation and drawing conclusions. As an Islamic educational institution, SD IT Darul Hasan apart from creating an intelligent generation is also obliged to prepare an Islamic generation that is religious and has good morals and character. The habit that is applied in humanist learning is that there is a welcoming and sayingonara program, which aims for students to have a disciplined attitude, pray Duha together before studying, recitations and routine memorization. The learning model applied is PAIKEM, active learning and team teaching. Places for learning are not only in the room, but also on the terraces, school fields, parks and prayer rooms and other school environments. The implemented curriculum is the national curriculum and is adapted to the unique curriculum of JSIT (integrated Islamic school network), and development is carried out so that it is more innovative and becomes a preferred learning. The learning activities that are applied are student-centered with the hope that students are able to find their own potential and have good character.